Coach behaviors and goal motives as predictors of attainment and well-being in sport - Smith, A. L. (Sport and exercise psychology research: From theory to practice, 2016)
Prompted by empirical evidence from organizational psychology, goal setting has been promoted as a fundamental skill for enhancing motivation and performance in sport and has enjoyed a central position in the sport psychology literature. However, equivocal findings in sport-specific studies have led to calls for further empirical examination of goal setting in sport to ensure a sound evidence base. In response, recent research has specifically explored the motivational processes underlying athletes` goal striving, and the role of coach behaviors in shaping athletes` goals. Grounded in Self-Determination Theory, this research proposes the Self-Concordance Model as a framework for examining the process from goal selection to attainment, as well as the implications for psychological and physical well-being. This chapter will present an overview of goal motive research in sport to date, highlighting recommendations for applied practice. Furthermore, the chapter will outline recent and future directions for empirical study including the examination of athletes` responses when faced with difficult and unattainable goals. (übern.)